CHILD LANGUAGE ACQUISITION IN THE EARLY LINGUAL PERIOD OF AGE 1- 2.5 YEARS (STUDY PHONOLOGY) (PEMEROLEHAN BAHASA ANAK PADA PERIODE LINGUAL DINI USIA 1- 2,5 TAHUN (KAJIAN FONOLOGI) - Dwinitia, Suci (Universitas PGRI Sumatera Barat, 2018)
Language acquisition is one of the interesting things to study. The language acquisition of each child cannot be equated with each other even though they are in the same period of development. This study aims to describe the phonemes that are spoken by children who are in the period of early lingual development (ages 1- 2.5 years). The method used in this study is a descriptive method with a qualitative approach. The data in this study are derived from the speech of two children who are in the period of early lingual development. Data was collected by recording children's expressions and taking notes in a note. Based on the results of data analysis and discussion it is known that children in the period of early lingual development have been able to pronounce the phonemes of language. All vowel phonemes [a], [i], [u], [e], [o] have been pronounced well. While the consonant phonemes are pronounced only phonemes [b], [c], [d], [h], [j], [k], [l], [m], [n], [p], [s] , [t], [w], [ŋ], and [ň]. Some of the phonemes spoken by these children have been pronounced well and some are still not right. The sequence of acquisition of these phonemes has followed the sequence of universally applicable phonological acquisition. Every child gets different sounds even though they are in the same period of development.